Interactions between smoking, increased serum levels of anti-CCP antibodies, rheumatoid factors, and erosive joint disease in patients with early, untreated rheumatoid arthritis. (January 2015) - Krol, A; Garred, P; Heegaard, NHH; Christensen, AF; Hetland, ML; Stengaard-Pedersen, K; Junker, P; Madsen, HO; Lottenburger, T; Ellingsen, T; Andersen, LS; Hansen, I; et al.
Abstract : Objectives: To determine to what extent shared epitopes, smoking, and anti-cyclic citrullinated peptide (anti-CCP) antibodies are associated with disease activity and erosive disease in patients with rheumatoid arthritis (RA) at disease onset. Method: RA patients not previously treated with disease-modifying anti-rheumatic drugs (DMARDs) and with a disease duration of < 6 months (CIMESTRA study) were examined for shared epitopes, anti-CCP antibodies, immunoglobulin M rheumatoid factor (IgM-RF) and IgA-RF, radiographic erosive changes in hands and feet, and clinical disease activity. Results: The study comprised 153 patients, of whom 104 (68%) were ever-smokers. The prevalence of patients with 0, 1, or 2 shared epitopes was 40 (48%), 71 (49%), and 33 (23%), respectively. Anti-CCP antibodies, IgM-RF, and IgA-RF were present in 89 (58%), 99 (65%), and 82 (54%) patients, respectively. Among smokers, erosive disease was associated with anti-CCP antibodies [odds ratio (OR) 3.9, 95% confidence interval (CI) 1.6–9.3], IgM-RF (OR 4.9, 95% CI 1.9–12), and IgA-RF (OR 2.8, 95% CI 1.2–6.4) but absent with regard to shared epitopes. Among never-smokers, erosive disease was not associated with either shared epitopes or antibodies. All antibody levels measured were associated with smoking and shared epitopes. Conclusions: Shared epitopes and smoking were associated with the production of anti-CCP antibodies and rheumatoid factors of IgM and IgA isotypes, which again were associated with erosive disease at presentation only in smokers. As shared epitopes and smoking were not directly associated with erosive disease, smoking may enhance the development of erosive disease in RA at different levels or through separate pathways.